Estudo da produção de espécies reativas de oxigênio em subpopulações de monócitos de pacientes infectados pelo Plasmodium vivax - Suelen Queiroz Diniz (2015)
Malaria is considered one of the most prevalent diseases in the world. According with World Health Organization, malaria affects approximately 400 million people a year. Although the incidence of the disease has decreased remarkably in recent years, malaria is still one of the greatest public health problems in Brazil and worldwide. During the disease, the etiologic agent Plasmodium spp. triggers the production of high levels of inflammatory cytokines. Data from our group and others indicate the importance of monocytes in the control and pathogenesis of malaria, once they are the major source of pro-inflammatory cytokines during the infection. Monocytes are heterogeneous and can be divided into three distinct subsets described based on their expression of CD14 and CD16. These cells are referred to as, classical (CD14+CD16-), inflammatory or intermediate (CD14highCD16+) and patrolling (CD14lowCD16+) monocytes. Given the importance of monocytes during malaria, the aim of our study is to define the role of the monocyte subsets during P. vivax infection. To address this question, we phenotypically and functionally characterized the classical, inflammatory, and patrolling monocytes present in the peripheral blood from patients experiencing acute malaria episodes. We first evaluated the ultra-structural features and mitochondria activity of monocyte subpopulations. Once they display distinct characteristics, we also assessed total and mitochondrial reactive oxygen species (ROS) production. Our data show that CD14highCD16+ monocytes in malaria patients displays increased mitochondrial activity and produce higher ROS level than the others subsets, suggesting a differential metabolic activity during P. vivax infection.